PARTISIPASI MASYARAKAT DALAM PELAKSANAAN MUSYAWARAH RENCANA PEMBANGUNAN DESA DI DESA TITIAN MODANG KOPAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2017 - Perdana, Muhammad Firman; Laksmono, Bambang Shergi; Harto, Syafri; Ismandianto, Ismandianto (UIR PRESS, 2019)
Village as a government that directly related to the community is the main focus in government development, because most of Indonesia's territory is in the countryside. Therefore, in village development it needs to be directed at the realization of an